Kinoform Optics: Single‐Step 3D Nanofabrication of Kinoform Optics via Gray‐Scale Focused Ion Beam Lithography for Efficient X‐Ray Focusing (Advanced Optical Materials 6/2015). Issue 6 (June 2015) - Keskinbora, Kahraman; Grévent, Corinne; Hirscher, Michael; Weigand, Markus; Schütz, Gisela
<x xml:space="preserve">Abstract</x> A kinoform lens designed for X‐ray point focusing, fabricated via grayscale ion‐beam lithography, is shown by C. Grévent and co‐workers. A high‐quality, continuous surface profile leads to almost 90% of the theoretical focusing efficiency, demonstrated on page 792 for soft X‐rays. This result paves the way to true kinoform X‐ray lenses for high‐energy electromagnetic radiation focusing with a very high efficiency.